Contextualization of Arabic Language Learning in the Framework of Religious Moderation in the Contemporary Era on the MTs Negeri 1 Ponorogo - Ajizah, Ratna Utami Nur; Jauhari, Irfan (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
This research discusses the significance of teaching the Arabic language with a moderation approach within the context of learning at MTs Negeri 1 Ponorogo. Employing a qualitative and case study approach, the research will discuss the implementation of contextualizing Arabic language instruction with a moderation perspective. It involves Arabic language teachers and VIII Class students in MTs Negeri 1 Ponorogo. Data were collected through classroom observations, interviews with teachers and students, and content analysis of instructional materials. The research findings reveal that the integration of moderation principles into Arabic language instruction yields positive outcomes. Students are more engaged in learning and comprehend how religious values can be applied in everyday situations. This approach enhances students' understanding of the Arabic language and moderation values. Moreover, it helps students develop inclusive, tolerant, and respectful attitudes towards religious and cultural diversity. Additionally, the utilization of multimedia materials and in-depth discussions enriches the learning process. This research offers practical guidance for the development of an adaptive and relevant educational approach that combines Arabic language learning with moderation values. It contributes to shaping a generation capable of effective Arabic communication and fostering inclusive attitudes in an increasingly diverse society.